Effect of particle size on maximum energy product of waste-derived ferrites - Woon, Hai Song; Ewe, Lay Sheng; Lim, Kean Pah; Ismail, Ismayadi; Tan, C. Y.; Wong, Y. W. (IOP Publishing, 2018)
Ferrite is an important component for electric motors, loud-speakers, EMI suppressors and transformer core. Hematite (Fe2O3) and strontium carbonate are commonly used to prepare ferrite. In this work, waste-derived hematite powder was milled using ball mill, high-energy milling and high-energy blender and the powder size was observed. The samples was further filtered according to different particle size, namely mesh 20, mesh 100 and mesh 400, and used as starting materials in the synthesis of strontium hard ferrites. Maximum energy product (BH)max of the ferrites was analyzed by a B-H tracer. The results showed that the maximum energy product is significantly affected by particle size of the starting materials. As anticipated, the maximum energy product is inversely proportional to the particle size and the hard ferrite produced by high-energy blender obtained 0.99 MGOe. With that, it is confirmed that permanent magnets derived from waste materials is also affected by its particle size. Other magnetic properties such as remanence and coercivity are also reported in this paper.